The art of winning commitment : 10 ways leaders can engage minds, hearts, and spirits - Richards, Dick, 1943- (AMACOM, 2004)
Annotation With this three-part approach, leaders will gain commitment from employees by tapping into their minds and hearts. Interviews with leaders-including a rabbi, a conductor and a Chief of the Cherokee Nation, as well as individuals such as Robert Redford, Oprah Winfrey and Phil Jackson-illustrate techniques for improving relationships and productivity and for gaining motivated employees.
Keywords: Employee motivation.; Employee loyalty.; Organizational commitment.; Commitment (Psychology); elektronické knihy; electronic books